Effect of layering sequence and ambient temperature on thermal insulation of multilayer high bulk nonwoven under extreme cold temperatures. Issue 2 (June 2022) - Dupade, Vikrant; Kumari, Ranjna; Premachandran, Balachandran; Rengasamy, Raju Seenivasan; Talukdar, Prabal
In extreme cold weather clothing ensemble, multiple layers of high bulk nonwovens are used to provide thermal insulation to the wearer. In this work, the effect of layering sequence in multi-layered high bulk thermal bonded nonwoven assembly on its thermal resistance is evaluated experimentally under sub-zero temperatures. Two multi-layered nonwovens, one made up of 1.4 denier solid (1.4 D S), 6 denier hollow (6 D H) and 15 denier hollow (15 D H) and the second made up of 3 denier hollow (3 D H), 6 denier hollow (6 D H) and 15 denier hollow (15 D H) polyester fibres were studied. The experiments were performed in a climatic chamber in the temperature range of 310 K to 210 K. Numerical simulations were carried out assuming heat transfer through the nonwovens as one-dimensional coupled conduction-radiation. The numerical methodology was developed using theoretical relations available in the literature to estimate the steady-state temperature profiles through the nonwoven layers and were validated using experimental data. The concurrence of experimental and numerical temperature profiles justifies the numerical methodology adopted in this work. Thermal resistance provided by the high bulk nonwoven increases with a decrease in ambient temperature. It is found that the thermal conductivity of nonwoven layers decreases from inner-to outer layers at a given ambient temperature. The heat flux through nonwoven layers, overall thermal conductivity and the thermal resistance of multi-layer nonwoven are independent of layering sequence if the convective heat transfer is extremely low.